AKIBAT HUKUM DARI PERKAWINAN CAMPURAN ANTARA JESSICA ISKANDAR DENGAN LUWIG DITINJAU DARI PERSPEKTIF HUKUM PERDATA INTERNASIONAL - Dewi, Aisyah Lashinta; Rosiana, Susi; Sari, Lia; Salsabila, Salma Rifda; Hidayati, Laila Nurul; Rakha, Agung (Cahaya Ilmu Bangsa, 2024)
The mixed marriage between Jessica Iskandar, an Indonesian citizen, and Ludwig Franz Willibald, a German nobleman, raises various interesting legal issues to be reviewed from the perspective of international civil law. This study aims to examine the legal aspects related to the mixed marriage, including the validity of the marriage, the jurisdiction of the court, the consequences of divorce, as well as the legal implications for the citizenship status and civil rights of both parties both after marriage and after divorce. In this analysis, a normative juridical approach is used by referring to various relevant national and international laws and regulations, and related literature. The results show the complexity in the enforcement of international civil law related to mixed marriages, especially in terms of marital status recognition and settlement of legal disputes between countries. This research is expected to contribute to the understanding and resolution of legal issues arising from mixed marriages, as well as provide recommendations for policy makers and legal practitioners in handling similar cases in the future.